2005
DOI: 10.1161/circulationaha.105.561423
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ejection Fraction on Cardiovascular Outcomes in a Broad Spectrum of Heart Failure Patients

Abstract: Background-Left ventricular function is a principal determinant of cardiovascular risk in patients with heart failure. The growing number of patients with preserved systolic function heart failure underscores the importance of understanding the relationship between ejection fraction and risk. Methods and Results-We studied 7599 patients with a broad spectrum of symptomatic heart failure enrolled in the Candesartan in Heart failure: Assessment of Reduction in Mortality and morbidity (CHARM) Program. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
534
8
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 744 publications
(610 citation statements)
references
References 24 publications
52
534
8
16
Order By: Relevance
“…To put this into context, previous investigations have shown that each 10 point decrease in ejection fraction below 45% is related to a 30% increase in death rate (HR 1.31, 95% CI, 1.24 to 1.38), after adjusting for other potent risk factors (including, for example, the New York Heart Association heart failure classification) over a median of 38 months of follow-up. 3 However, it is important to note that our findings do confirm this strong relation between ejection fraction and increasing poor outcomes. Additionally, our findings are dependent on the specific time frame of prediction (ie, 5 years) that we used; a shorter time frame may have suggested stronger predictive value for echocardiogram findings.…”
Section: Original Research and Contributionssupporting
confidence: 72%
See 1 more Smart Citation
“…To put this into context, previous investigations have shown that each 10 point decrease in ejection fraction below 45% is related to a 30% increase in death rate (HR 1.31, 95% CI, 1.24 to 1.38), after adjusting for other potent risk factors (including, for example, the New York Heart Association heart failure classification) over a median of 38 months of follow-up. 3 However, it is important to note that our findings do confirm this strong relation between ejection fraction and increasing poor outcomes. Additionally, our findings are dependent on the specific time frame of prediction (ie, 5 years) that we used; a shorter time frame may have suggested stronger predictive value for echocardiogram findings.…”
Section: Original Research and Contributionssupporting
confidence: 72%
“…3 Other studies, however, have demonstrated that higher ejection fraction values are associated with worse outcomes than lower values among patients with preserved left ventricular function. 4 In this study, we examine the predictive value of echocardiogram measurements, including both ejection fraction and left ventricular wall thickness so as to further clarify these risks.…”
Section: Original Research and Contributionsmentioning
confidence: 98%
“…In this respect, there was a clear indication for left ventricular reconstruction after LV aneurysm in our study patients. In the CHARM study (The Candesartan in Heart failure: Assessment of Reduction in Mortality and morbidity), which included a study population of 7599, a 10% decrease in EF (in patients with an EF < 45%) was found to be associated with a 39% higher mortality risk [23] . The STICH study (surgical treatment of ischemic heart failure) is another example of a study that found a significant increase in ejection fraction after aneurysm repair in patients with an akinetic or dyskinetic ventricle following myocardial infarction and who were investigated with regard to possible advantages of additional ventricular reconstruction versus coronary bypass alone.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it is well recognised that correlation of those two parameters is not very strong, partly because: 1) stroke volume depends not only on LVEF but also on LV end-diastolic volume and LV loading conditions, 2) LV filling pressures are related not only to its systolic but also to its diastolic function, and 3) LVEF as a sole parameter does not fully reflect LV systolic function [3]. The association of LVEF with survival is not linear as it is most markedly expressed in patients with severely reduced LVEF; once elevated above 45% LVEF does not further contribute to the estimation of cardiovascular outcomes in HF [28].…”
Section: Genetic Testingmentioning
confidence: 99%